2017
DOI: 10.7897/2230-8407.08690
|View full text |Cite
|
Sign up to set email alerts
|

Antidiabetic Plants in Traditional Medicines: A Review

Abstract: Plant extracts and their constituents are one of the potential approaches those are used for the prevention and treatment of a huge number of disorders. Herbal products and food supplements are the chief components of plant extracts, those are helpful in retaining healthiness, performing against a range of diseases and they support the quality of being. Diabetes mellitus is, a multi-factorial chronic metabolic ailment causes high blood glucose level, one of them. The systematic researches of traditional herbal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…Apropos of naphthoquinones, they are important secondary metabolites having therapeutic value that are commonly found in various Diospyros species [48]. In this context, the detection of the trigonelline–nicotinic acid combination, only detected in D. rekoi LEs was also interesting, considering that trigonelline, a pyridine alkaloid derived from nicotinic acid [49], has been reported to have a potent anti-diabetic effect, similar to naphthoquinones [50,51]. Approximately 100 trigonelline-forming plant species have been identified, including D. mollis [49,52].…”
Section: Discussionmentioning
confidence: 99%
“…Apropos of naphthoquinones, they are important secondary metabolites having therapeutic value that are commonly found in various Diospyros species [48]. In this context, the detection of the trigonelline–nicotinic acid combination, only detected in D. rekoi LEs was also interesting, considering that trigonelline, a pyridine alkaloid derived from nicotinic acid [49], has been reported to have a potent anti-diabetic effect, similar to naphthoquinones [50,51]. Approximately 100 trigonelline-forming plant species have been identified, including D. mollis [49,52].…”
Section: Discussionmentioning
confidence: 99%
“…Our research group successfully developed methods for the removal of various pollutants such as Cr(VI) [1][2][3][4], Zn(II) [5], Al(III) [6][7][8][9], F - [10][11][12][13][14][15], NO 2 - [16,17], NH 3 [18][19][20], PO 4 3- [21,22] and dyes [23][24][25] based on the adsorbents derived from various plants.…”
Section: Introductionmentioning
confidence: 99%
“…INTRODUCTION: Multifactorial metabolic diseases, for example, diabetes build up several complications such as immunodeficiency, hyperlipidemia, and hepatic toxicity, etc. 1 Fact from ethnopharmacological studies have shown that Citrullus colocynthis is traditionally used as antibacterial, antifungal, antiviral, hepatoprotective, anti-inflammatory, anti-diabetic, antioxidant and anticancer agent 2,3 . The proposed theory is phytosomes of crude drug extract of Citrullus colocynthis will be more effective and safe as an anti-diabetic agent.…”
mentioning
confidence: 99%